The prognostic value of PTEN, p53, and beta-catenin in endometrial carcinoma: a prospective immunocytochemical study. Issue 3 (1st May 2007) - Athanassiadou, P.; Athanassiades, P.; Grapsa, D.; Gonidi, M.; Athanassiadou, A. M.; Stamati, P. N.; Patsouris, E.
Abstract : Mutations of the PTEN, p53, and beta-catenin genes are the most frequent molecular defects in endometrial carcinomas. The aim of this study was to investigate their prognostic significance in this form of cancer. Imprint smears were obtained from 80 fresh endometrial tumor specimens and studied immunocytochemically for the expression of PTEN, p53, and beta-catenin proteins. The staining pattern was correlated with several well-established prognostic parameters, including 5-year survival. Positive staining of p53 was significantly correlated with increased stage ( P < 0.0001), lymph node metastases ( P = 0.001), and a nonendometrioid histology ( P = 0.001). On the contrary, positive beta-catenin expression was significantly associated with decreased stage ( P = 0.002), decreased grade ( P = 0.007), and a negative lymph node status ( P = 0.023). PTEN positivity was correlated with decreased stage ( P = 0.002) and negative lymph nodes ( P = 0.008). All the three markers affected survival significantly in univariate analysis but only beta-catenin had an independent prognostic impact. An independent prognostic significance was also shown for PTEN in the stage I subgroup of patients. The results of our study indicate that loss of beta-catenin expression is a strong and independent predictor of an unfavorable outcome in patients with endometrial carcinoma. Loss of PTEN may also be associated with a worse prognosis in patients with early-stage disease.